Alginate Formulations: Current Developments in the Race for Hydrogel-Based Cardiac Regeneration - Cattelan, Giada; Guerrero Gerbolés, Amparo; Foresti, Ruben; Pramstaller, Peter P.; Rossini, Alessandra; Miragoli, Michele; Caffarra Malvezzi, Cristina (Frontiers in Bioengineering and Biotechnology, 2020)
Cardiovascular diseases, including myocardial infarction, represent the main worldwide cause of mortality and morbidity. In this scenario, to contrast the irreversible damages following myocardial infarction, cardiac regeneration has emerged as a novel and promising solution for in situ cellular regeneration, preserving cell behavior and tissue cytoarchitecture. Among the huge variety of natural, synthetic, and hybrid compounds used for tissue regeneration, alginate emerged as a good candidate for cellular preservation and delivery, becoming one of the first biomaterial tested in pre-clinical research and clinical trials concerning cardiovascular diseases. Although promising results have been obtained, recellularization and revascularization of the infarcted area present still major limitations. Therefore, the demand is rising for alginate functionalization and its combination with molecules, factors, and drugs capable to boost the regenerative potential of the cardiac tissue. The focus of this review is to elucidate the promising properties of alginate and to highlight its benefits in clinical trials both in relation to cardiac regeneration. The definition of hydrogels, the alginate characteristics, and recent biomedical applications are herewith described. Afterwards, the review examines in depth the ongoing developments to refine the material relevance in cardiac recovery and regeneration after myocardial infarction (MI) and presents current clinical trials based on alginate.